Physical and chemical characteristics and fatty acids composition of seeds oil isolated from Camelina sativa (L) cultivated in Mongolia - Chantsalnyam, B; Otgonbayar, Ch; Enkhtungalag, O; Odonmajig, P (Mongolian Journal of Chemistry, 2014)
Camelina sativa L is a cruciferous oilseed plant. This plant is cultivated as an oilseed crop mainly in Europe and in North America and over the past years the cultivation has arranged in our country. The analyzed oil is obtained from the seeds of Camelina sativa L, growing in Bornuur, Tuv province. The goal of this study was to determine the physical and chemical characteristics and fatty acids composition of Camelina sativa L seed oil cultivated in Mongolia. According to our analysis total lipid was determined 38.52 %, moisture 4.80 % and total mineral elements 4.02 %, respectively. Mineral elements in Camelina sativa L seeds contain calcium (0.56 %), phosphorous (1.22 %), potassium (1.39 %), magnesium (0.53 %) in dominated amounts; iron, zinc, manganese and copper in trace amounts. Eight nonessential amino acids in seeds of this plant with total amount of 75.9 % were identified; phenylalanine was detected in highest amount among the all identified amino acids, while lysine, tryptophan and arginine are followed. The following characteristics in Camelina sativa seeds oil were determined. The refractive index was 1.4774 at 20°C, the peroxide value of fresh oil was 0.03 meq H2O2 /kg, saponification value 185.8 mg KOH/g, iodine value 143.33 g J2 and acidic value 6.27 mg KOH /g. Carotenoid was determined as 16.77 mg %, by spectrometry in Camelina sativa seeds oil. The analysis of fatty acids composition showed that there are 12.5 % saturated and 87.5 % unsaturated fatty acids. In particular, oleic acid (C18:1) 14.0 %, linoleic acid (C18:2) 9.0 %, α-linolenic acid (C18:3) 10.5 % and gondoic acid (C20:1) 32.8 %, were composed the major part of unsaturated fatty acids. DOI: http://dx.doi.org/10.5564/mjc.v14i0.205 Mongolian Journal of Chemistry 14 (40), 2013, p80-83